PROSPEROUS OF POTTERY INDUSTRY AND THE ARTISANS OF MANAMADURAI - Akilandeeswari, S.V.; Pitchai, C. (International Journal of Research -GRANTHAALAYAH, 2016)
In India, over 260 million live in poverty. Poverty is because of high level unemployment, underemployment, low level of income and increase in debt. Developing rural economy is a prime concerns for every developing country. Continuously efforts were made for improving the social and economic well-being of rural people. The Department of Rural Development within the Ministry of Rural Development has been organized for upliftment of the rural people. Many programmes and schemes have been implemented for the development of rural economy. The schemes aim at generating employment, eliminating poverty, developing infrastructure, social security to the rural mass. Pottery is one of the oldest industries which provide employment to rural people. This sector is characterized by low investment, operational flexibility, local resources and domestic and export opportunity. An object of art made of a composition of clay and sand and baked with earthen color, is Pottery. A cottage industrial society in Manamadurai, more than 120 families of artisans are producing pottery crafts. The economy of this village largely depends on pottery industry. So a study has been made in Manamadurai Pottery Workers Cooperative society to analyze the problem of artisans and rejuvenate the industry.